Towards a sequence stratigraphic solution set for autogenic processes and allogenic controls: Upper Cretaceous strata, Book Cliffs, Utah, USA - Hampson,GJ (Journal of the Geological Society, 2016)
Upper Cretaceous strata exposed in the Book Cliffs of east–central Utah are widely used as an archetype for the sequence stratigraphy of marginal-marine and shallow-marine deposits. Their stratal architectures are classically interpreted in terms of accommodation controls that were external to the sediment routing system (allogenic), and that forced the formation of flooding surfaces, sequence boundaries, and parasequence and parasequence-set stacking patterns. Processes internal to the sediment routing system (autogenic) and allogenic sediment supply controls provide alternatives that can plausibly explain aspects of the stratal architecture, including the following: (1) switching of wave-dominated delta lobes, expressed by the internal architecture of parasequences; (2) river avulsion, expressed by the internal architecture of multistorey fluvial sandbodies and related deposits; (3) avulsion-generated clustering of fluvial sandbodies in delta plain strata; (4) ‘autoretreat’ owing to increasing sediment storage on the delta plain as it lengthened during progradation, expressed by progradational-to-aggradational stacking of parasequences; (5) sediment supply control on the stacking of, and sediment grain-size fractionation within, parasequence sets. The various potential allogenic controls and autogenic processes are combined to form a sequence stratigraphic solution set. This approach avoids anchoring of sequence stratigraphic interpretations on a specific control and acknowledges the non-unique origin of stratal architectures.